2018
DOI: 10.3390/su10061973
|View full text |Cite
|
Sign up to set email alerts
|

A Derivation of Factors Influencing the Successful Integration of Corporate Volunteers into Public Flood Disaster Inquiry and Notification Systems

Abstract: Flood hazards have become increasingly common and serious over the last few centuries. Volunteers can observe instant flood information in their local environment, which presents a great opportunity to gather flood information. The information provided by individual volunteers is too much for them to truly understand. Corporate volunteers can offer more accurate and truthful information due to their understanding of the roles and requirements of specific tasks. Past studies of factors influencing the success o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 88 publications
0
25
0
2
Order By: Relevance
“…Based on the information presented from prior researches (Bannari et al n.d.;Darabi et al 2019;Yang et al 2018) , it has enough knowledge that helps to identified and recognized the seven important flash flood susceptibility factors, that it has been used in this study case which, are soil moisture index (SMI), rainfall, drainage density, Lulc, altitude, slope, and soil.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Based on the information presented from prior researches (Bannari et al n.d.;Darabi et al 2019;Yang et al 2018) , it has enough knowledge that helps to identified and recognized the seven important flash flood susceptibility factors, that it has been used in this study case which, are soil moisture index (SMI), rainfall, drainage density, Lulc, altitude, slope, and soil.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Managers should follow the model suggested by Marimon et al [57] by showing volunteers that they are personally engaged in the mission, help volunteers understand how the mission is important in fulfilling their contributions to society, make sure that volunteers understand the mission thoroughly, aid volunteers in understanding how colleagues are engaged with the mission, and allow volunteers to help update the mission over time. As one of the main motivations of volunteers is to perform activities important for society [1,[5][6][7], they should be very receptive to such actions on the part of managers.…”
Section: Discussionmentioning
confidence: 99%
“…Volunteering builds people's capacity, social inclusion, and responsiveness to societal initiatives [4]. In addition, volunteers play an important role in initiatives to promote sustainability, or development which fulfils the needs of the present generation without hurting needs of future ones [5][6][7]. Given the prevalence and value of volunteering, understanding volunteer dynamics has accordingly become more critical.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention should be given to possible renegotiations of PPP's contracts and performance of future infrastructure. These problems should be addressed to ensure that PPP will help to overcome the large-scale deficit in infrastructure investments [52,53].…”
Section: Ppp In Russia and International Experiencementioning
confidence: 99%
“…In addition, the experience of implementing public-private interaction is integrated into international and national public legislation [20]. At the same time, the combination of public and private interests through the creation of a unified legal framework is not an easy task, which is connected with the complexity of social relations that are to be settled [53].…”
Section: Sustainable Developmentmentioning
confidence: 99%